A compact design for an electric driven hydraulic gear machine capable of multiple quadrant operation. (November 2022) - Zappaterra, Federico; Vacca, Andrea; Sudhoff, Scott D.
Highlights: Integrating hydraulic and electric machines leads to greater power density. Electrification allows novel throttle less actuator control strategies. Electro-hydraulic drives allow energy recovery. The hydraulic gear machine optimal rotation speed needs to be increased. Abstract: This paper presents an innovative design of an integrated electro-hydraulic (EH) flow generation unit able to operate in multiple quadrants. The proposed unit is composed of a hydraulic machine which can operate in either pumping or motoring mode, and an electric machine, which can operate as electric motor or generator. The adopted morphological integration of the two unit fulfills the goals of maximizing compactness, power to weight ratio, energy efficiency and quietness. The design results from a numerical optimization procedure that includes detailed simulation of both the electric machine and the hydraulic machine, using simulation tools previously developed by the authors, but combined for the first time in this work. After describing the optimization procedure, the paper focuses on the design integration aspects of the novel unit. A 9 kW prototype of the integrated unit was also fabricated and tested to verify its performance. Tests results show a measured overall energy efficiency up to 69%, demonstrating the potentials of the proposed concept, despite some limitations present in the first prototypes which could be addressed in future design refinements.